2017
DOI: 10.1186/s12977-017-0341-x
|View full text |Cite
|
Sign up to set email alerts
|

Prototype foamy virus elicits complete autophagy involving the ER stress-related UPR pathway

Abstract: BackgroundPrototype foamy virus (PFV) is a member of the Spumaretrovirinae subfamily of retroviruses, which maintains lifelong latent infection while being nonpathogenic to their natural hosts. Autophagy is a cell-programmed mechanism that plays a pivotal role in controlling homeostasis and defense against exotic pathogens. However, whether autophagy is the mechanism for host defense in PFV infection has not been investigated.FindingsOur results revealed that PFV infection induced the accumulation of autophago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 47 publications
(45 reference statements)
2
15
0
Order By: Relevance
“…The surge in protein synthesis during viral replication frequently overloads the endoplasmic reticulum, resulting in ERS [23] that triggers the unfolded protein response (UPR) to restore protein homeostasis and decrease aggregates of misfolded peptides. However, persistent UPR due to severe ERS can lead to apoptosis [24]. Consistent with this, the 143B cells treated with ZSTK474 or VSVΔ51 showed markedly swollen endoplasmic reticulum within 24 h, which increased further in the dual treated cells ( Fig.…”
Section: The Synergistic Effect Of Zstk474 and Vsvδ51 Depends On Ers-supporting
confidence: 77%
“…The surge in protein synthesis during viral replication frequently overloads the endoplasmic reticulum, resulting in ERS [23] that triggers the unfolded protein response (UPR) to restore protein homeostasis and decrease aggregates of misfolded peptides. However, persistent UPR due to severe ERS can lead to apoptosis [24]. Consistent with this, the 143B cells treated with ZSTK474 or VSVΔ51 showed markedly swollen endoplasmic reticulum within 24 h, which increased further in the dual treated cells ( Fig.…”
Section: The Synergistic Effect Of Zstk474 and Vsvδ51 Depends On Ers-supporting
confidence: 77%
“…PERK activation contributes to DENV and BTV replication by inducing autophagy and promoting survivability of virusinfected cells (17,31,32). However, PFV infection activates PERK pathway, thereby inducing autophagy, which in turn represses PFV replication (33). PERK pathway also inhibits influenza virus replication by reducing viral protein synthesis (28).…”
Section: Discussionmentioning
confidence: 99%
“…Our earlier study showed that PFV induces complete autophagy and is associated with endoplasmic reticulum (ER) stress (13). We report here that PFV Gag recruits ESCRT to promote amphisome formation and facilitate endosomal autophagic clearance of SGs.…”
mentioning
confidence: 71%
“…Also, the PFV L-domain is critical for the recruitment of tumor susceptibility gene 101 (TSG101) and apoptosis-linked gene 2 protein (ALG-2)-interacting protein X (Alix), the key factors of the ESCRT pathway, and promotes viral budding (12). Previously, we found that PFV induces autophagy, which is a membrane-associated biological process, as is viral budding (13). However, whether PFV Gag is a key factor in PFV-induced autophagy remains unknown.…”
mentioning
confidence: 99%